Community-Based HIV and Viral Hepatitis Fellowship Evaluation: Results from a Qualitative Study. (November 2022) - Bolduc, Philip; Day, Philip G.; Behl-Chadha, Bittie; Karapanos, Melissa; Carson-Sasso, Vanessa; Simpson, E. Hatheway; Hebert, Scott
Purpose: The UMass Chan Medical School/New England AIDS Education and Training Center Community-Based HIV and Viral Hepatitis Fellowship was launched in 2014 to train physicians and nurse practitioners to become experts in outpatient management of HIV, hepatitis B and C, and latent tuberculosis. The purpose of this study was to identify areas of strength and improvement and understand fellows' perceptions of the program and its impact on their current positions and career trajectories. Methods: Qualitative study utilizing a semi-structured interview guide with (11) fellowship graduates (8 MDs; 3 NPs). 45 to 60 min interviews were conducted in April and May 2021, recorded and transcribed. Transcripts were analyzed for representative themes and general patterns in the data. Results: Results indicate high satisfaction with the fellowship, which left a positive and indelible impact on their careers and patient care. Fellows highlighted the program's commitment to health equity, its role in transforming them into leaders and advocates for HIV in primary care, and their ability to balance their work and training demands with their personal lives and needs. The fellowship motivated them to become more involved in public health initiatives, serve marginalized communities and reduce their health disparities. They expressed confidence in their ability to independently manage outpatient HIV, viral hepatitis B and C, and latent tuberculosis, and found areas of overlap with their work in primary care. Conclusion: As the care of people with HIV becomes more commonplace in primary care clinics, it is imperative that primary care providers receive the necessary training and education to meet this need. Our study of 11 former fellows shows that the Community-Based HIV and Viral Hepatitis Fellowship offers such training, spreads it to other institutions, and can be a model for other programs nationwide.